Applying micro – teaching and jugyou kenkyuu (lesson study) to enhance students’ teaching skills through the module of Geopraphy teaching methodology at high school - Ha , Van Thang (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This article provides some basic theoretical statements about micro-teaching and lesson study, and suggests how to combine these methods to develop the teaching skills of students in a High School Geography Teaching Methodology module in a Department of Geography. After trailing this combination, the author analyzed data from the trial to assess the feasibility of applying these two methods to teacher training programmes